2012
DOI: 10.5897/ajest12.124
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selected heavy metals in inland fresh water of lower River Niger drainage in North Central Nigeria

Abstract: The concentrations of some ferruginous ore associated heavy metals were determined in freshwater from River Niger. Water samples were collected from both upstream and downstream along the mainstream drainage channel, traversing past the steel production industry Ajaokuta between 2003 and 2005. The water samples were digested according to standard methods and tested for Cadmium (Cd), Manganese (Mn), Chromium (Cr), Nickel (Ni), Cupper (Cu), Zinc (Zn) and Lead (Pb) using Unicam 969 atomic absorption spectrophotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
16
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 16 publications
10
16
6
Order By: Relevance
“…This may be that the season is contributing to the concentration of Pb in River Benue while the station is not. The results of this study agrees with the finding of other studies that reported Pb beyond the permitted limits (Hong et al, 2014;Wangboje and Ekundayo, 2013;Olatunji and Osibanjo, 2012;Aderinola et al, 2009). The result of the seasonal variation of the Pb concentration in the water samples showed that the concentration of Pb during the dry season was higher compared to the rainy season.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This may be that the season is contributing to the concentration of Pb in River Benue while the station is not. The results of this study agrees with the finding of other studies that reported Pb beyond the permitted limits (Hong et al, 2014;Wangboje and Ekundayo, 2013;Olatunji and Osibanjo, 2012;Aderinola et al, 2009). The result of the seasonal variation of the Pb concentration in the water samples showed that the concentration of Pb during the dry season was higher compared to the rainy season.…”
Section: Discussionsupporting
confidence: 83%
“…This may be due to the fact that during the dry season, the quantity of the water is reduced and the concentration therefore increased. This result is similar to the findings of Olatunji and Osibanjo (2012) that reported higher values of Pb during the dry season in lower River Niger drainage in North central Nigeria. Across the stations, station V had the highest Pb concentration while station VI the lowest during the study period.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations